Comparative Study Between Permethrin-5% and Oral Ivermectin for the Treatment of Scabies - Naheed Khan; Majid Hussain; Bushra Muzaffar; Adeel Siddique; Rizwan Ali Khan; Tamoor Nazir (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare the efficacy of 5% Permethrin with the oral Ivermectin for management of scabies.